Virtual Spaces: Employing a Synchronous Online Classroom to Facilitate Student Engagement in Online Learning - McBrien, J. Lynn; Cheng, Rui; Jones, Phyllis (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2009)
This research study is a collaborative project between faculty in social foundations, special education, and instructional technology in which we analyze student data from six undergraduate and graduate courses related to the use of a virtual classroom space. Transactional distance theory (Moore & Kearsley, 1996) operates as our theoretical framework as we explore the role of a virtual classroom in distance education and analyze the ways in which a synchronous learning environment affects students’ learning experiences. Elluminate Live! was the software employed in the virtual classroom. In this analysis, particular themes emerged related to dialogue, structure, and learner autonomy. In addition, students rated convenience, technical issues, and pedagogical preferences as important elements in their learning experiences. The article discusses these themes as a contribution to reducing the “distance” that students experience in online learning and to developing quality distance education experiences for students in higher education.